Preparation and characterization of organogels containing vitamin E for cosmetic application - Martinez, Renata Miliani (2022)
Human skin is attacked daily by ultraviolet (UV) radiation and pollutants. Such aggressions can promote lipid peroxidation mediated by free radicals in cells, generating DNA damage and inflammatory processes, in addition to endogenous vitamin E depletion. The use of antioxidant cosmetic products has potential for treatment; however, the stability and permeation of these active ingredients may be a limiting factor in their use. Thus, the present work aimed at the development and characterization of organogels containing vitamin E and their dispersions in bigels, focusing on cosmetic application. The results derived from this investigation are ordered in three articles, being: (1) review on organogels in the cosmetic area; (2) application of organogels containing vitamin E in systems of bigels, their physicochemical characterization and evaluation of efficacy in vitro and ex vivo; and (3) characterization of organogels containing vitamin E regarding their microstructure and rheological profile. The results indicated that despite the potential for permeation of hydrophilic and hydrophobic actives through the skin, increased stability and sensory modification, organogels were still little explored in the cosmetic area. The bigels were characterized as weak viscoelastic oil-in-water gels, with adequate stability determined by thermal and centrifugal stress. The presence of vitamin E generated little influence on the rheological profile and efficacy in vitro and ex vivo of the bigels, emphasizing the need for further studies in the presence of stress in the biological sample. Organogels were characterized as weak pseudoplastic gels. The type of organogelling agent was relevantly influenced in the presence of vitamin E. 12-Hydroxysesteric acid had a reduction in gel strength, while candelilla wax showed increased strength. All phase transition temperatures were reduced in the presence of vitamin E. The results indicated the potential use of organogels and bigels in the delivery of vitamin E for topical application, enabling the development of formulations with stability and modulation of the rheological profile as needed.